Validation of smart contracts on the hyperledger fabric blockchain : a process mining approach - Suherman, Dennis Christopher (Nanyang Technological University, 2021)
The rise in popularity of blockchain and distributed ledger technologies has given rise to new benefits as well as challenges, especially in business domains. In particular, the trust inherent in the blockchain architecture due to the immutability of records contained within has allowed inter-organization cooperation to flourish as there is no longer a need for a trusted central counterparty. Such processes are normally executed by smart contracts; however, this very immutability also means that smart contracts loaded onto the blockchain must be bug-free and adhere fully to the business process as defined. To that end, this paper explores and defines a methodology for verification of smart contracts by detecting changes in the world state that are effected by the smart contract, performing process mining on the extracted data, and applying conformance checking methods against a process model defined in BPMN. By doing so, verification is able to proceed without knowledge of the implementation aspects of the smart contract. Adherence to the model process is both measured quantitatively, through a measure of fitness, as well as observed through a graphical representation.